Two managerial public relations roles in the South African context - Benita Steyn; Tery Everett (Communicare)
This article reports the findings of Stage 3 of an international collaborative research programme, its point of departure being that public relations (PR) roles researchers have largely ignored research in the management domain in their conceptualisation of the PR manager role. (The first qualitative stage was conducted in the US and UK, and the second, quantitative stage in the UK). In the third stage, the UK study was replicated in South Africa (SA) to map and compare the main elements of management performed by PR managers working globally in a range of organisational settings and in different cultural contexts (with a view to reconceptualising the PR manager role). While the UK research found five empirical PR roles, the final parsimonious 2-factor solution accepted in the SA study was labelled the strategic public relations manager (a strategic role at the macro or societal level), and the operational public relations manager (a functional role at the middle-management level).